Incidence of Infective Endocarditis among Haemodialysis Patients: Experience at a Single Centre in Bangladesh (Journal of Current and Advance Medical Research, 2021)
Background: Infection in hemodialysis is a very dangerous condition for the patients. Objective: The purpose of the present study was to find out the incidence of infective endocarditis among hemodialysis patients.Methodology: This was a cross sectional study which was conducted in the Department of Nephrology at Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh during the periods of July 2010 and June 2012. Hemodialysis patients who were attending in the Department of Nephrology at BSMMU, Dhaka were taken as study population.Results: A total number of 50 patients presented with hemodialysis. Out of 50 patients 34(68.0%) cases were male and 16(32.0%) cases were female. The mean with SD of age of the patients was 38.44±13.0 years with a range of 18 to 68 years. Out of 50 patients 6(12.0%) cases had positive blood culture of which 3 cases had shown Staphylococcus aureus, 1 case had Escherichia coli, 1 case had Enterococci species and 1 case had Salmonella typhi, Among the 50 patients 5 (10.0%) had vegetation on cardiac valve. The patients frequency of dialysis 2 times per week showed 01 (2.43%) positive blood C/S and 5 positive in 3 times per week showed 05 (55.55%) positive blood C/S (p>0.001).Conclusion: In conclusion infective endocarditis causes infection with high mortality among the patients of CKD undergoing hemodialysis.Journal of Current and Advance Medical Research, January 2021;8(1):54-58